2020
DOI: 10.3390/met10050626
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sand Fines Transport Velocity on Erosion-Corrosion Phenomena of Carbon Steel 90-Degree Elbow

Abstract: Erosion-corrosion is an ineluctable flow assurance problem confronted in hydrocarbon transportation and production systems. In this work, the effect of sand fines velocity on the erosion-corrosion behavior of AISI 1018 carbon steel long radius 90° elbows was experimentally and numerically investigated for liquid-solid flow conditions. Experiments were effectuated for sand fines of mean diameter 50 µm circulated in a flow loop with three different velocities (0.5, 1 and 2 m/s). To elucidate the erosion-corrosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Given the focal emphasis on wear depth within this comparative assessment, the alignment with the principles of the Oka wear model becomes particularly conspicuous. Wear rate to impact velocity at 0.5 m/s, 1 m/s, and 2 m/s from a 0.05 mm particle size on carbon steel (redrawn from [72]) in comparison to NiTi from this study.…”
Section: Validation Of the Numerical Simulation With Experimental Fin...mentioning
confidence: 93%
See 1 more Smart Citation
“…Given the focal emphasis on wear depth within this comparative assessment, the alignment with the principles of the Oka wear model becomes particularly conspicuous. Wear rate to impact velocity at 0.5 m/s, 1 m/s, and 2 m/s from a 0.05 mm particle size on carbon steel (redrawn from [72]) in comparison to NiTi from this study.…”
Section: Validation Of the Numerical Simulation With Experimental Fin...mentioning
confidence: 93%
“…Figure12. Wear rate to impact velocity at 0.5 m/s, 1 m/s, and 2 m/s from a 0.05 mm particle size on carbon steel (redrawn from[72]) in comparison to NiTi from this study.…”
mentioning
confidence: 94%
“…Erosion–corrosion in ductile metals has been investigated by many researchers, who found that it was due to the cutting action of the abrasive particles [ 5 , 6 ]. Erosion-induced damage is very much influenced by dispersed phase properties, particle impact conditions, and properties of the target material [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Erosion of pipeline components can cause serious malfunction for the hydrocarbon extraction and processing industries, as the sand produced can impact the walls of the pipeline, resulting in wear damage [1,2]. When the dispersed phase has to be transported, flow-changing devices, i.e., elbows, are inclined to erosion damage because of the redirected flow at curvature.…”
Section: Introductionmentioning
confidence: 99%